If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -7(9y + 7) = 1 + 3(-7 + -1y) Reorder the terms: -5y + -7(7 + 9y) = 1 + 3(-7 + -1y) -5y + (7 * -7 + 9y * -7) = 1 + 3(-7 + -1y) -5y + (-49 + -63y) = 1 + 3(-7 + -1y) Reorder the terms: -49 + -5y + -63y = 1 + 3(-7 + -1y) Combine like terms: -5y + -63y = -68y -49 + -68y = 1 + 3(-7 + -1y) -49 + -68y = 1 + (-7 * 3 + -1y * 3) -49 + -68y = 1 + (-21 + -3y) Combine like terms: 1 + -21 = -20 -49 + -68y = -20 + -3y Solving -49 + -68y = -20 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -49 + -68y + 3y = -20 + -3y + 3y Combine like terms: -68y + 3y = -65y -49 + -65y = -20 + -3y + 3y Combine like terms: -3y + 3y = 0 -49 + -65y = -20 + 0 -49 + -65y = -20 Add '49' to each side of the equation. -49 + 49 + -65y = -20 + 49 Combine like terms: -49 + 49 = 0 0 + -65y = -20 + 49 -65y = -20 + 49 Combine like terms: -20 + 49 = 29 -65y = 29 Divide each side by '-65'. y = -0.4461538462 Simplifying y = -0.4461538462
| y-9(5)=3 | | 4x^2+0.2x+0.01=0 | | 4(u+1)-7=3(u-1)+7 | | -x+3.9forx=-7.2 | | (4x+2)=-34 | | 9+4(-4)+3=-4 | | (4x+2)=34 | | 0.80x+0.20(60)=0.40(78) | | -3.6-7.2=12.7-6.1b | | (4x-2)(4x-2)+(5x)(5x)= | | 10x-4-6x=5x-7 | | (-10)+4=-2(-10)+-6 | | 2a+8=4a+16 | | 5(4x-4)-9=-31 | | 216=8(-5r-3) | | (3x+y*1)=(7*2x-3y) | | 29.95=42-sqrt(0.001x+2) | | (x^2+2xy)dx+xdy=0 | | 5w-6=60 | | 18=9x+4-2x | | (3+2x)=0.5x+1 | | 7x+10=4x-16 | | 3X=6-3 | | -19=v/10 | | 3x+3x-7=47 | | 2x[2+(5+2)]= | | ln(9x)=2ln(2x) | | 5(4x-4)-9=31 | | X-4y+15=0 | | -3x+4x-10=15x+1 | | 3n-2m=mn+4 | | X+7x=-24 |